2019
DOI: 10.3390/coatings9030200
|View full text |Cite
|
Sign up to set email alerts
|

Coating of Titanium Substrates with ZrO2 and ZrO2-SiO2 Composites by Sol-Gel Synthesis for Biomedical Applications: Structural Characterization, Mechanical and Corrosive Behavior

Abstract: The use of metallic materials as implants presents some major drawbacks, such as their harmful effects on the living organism, especially those induced by corrosion. To overcome this problem, the implant surface of titanium implants can be improved using a coating of bioactive and biocompatible materials. The aim of this work is the synthesis of SiO2/ZrO2 composites with different percentages of zirconia matrix (20, 33 and 50 wt.%), by the sol-gel method to coat commercial Grade 4 titanium disks using a dip co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…In particular, the diameter of the zone of inhibition of SiO 2 /PEG/CGA and SiO 2 /PCL/CGA were compared. The better antibacterial activity was observed when E. coli was treated with the hybrids containing PEG …”
Section: Resultsmentioning
confidence: 99%
“…In particular, the diameter of the zone of inhibition of SiO 2 /PEG/CGA and SiO 2 /PCL/CGA were compared. The better antibacterial activity was observed when E. coli was treated with the hybrids containing PEG …”
Section: Resultsmentioning
confidence: 99%
“…The control sample (i.e., bare glass without ZnO film) showed that some of the test strain was killed up to the first 4-h incubation time; however, the test strain proliferated after 24 h. Compared to the control, the synthesized ZnO film exhibited superior antibacterial activity, killing 99.8% or 99.9% (4-log reduction for S. aureus and 6-log reduction for E. coli ) of both test bacterial strains—irrespective of the incubation time. Given the antibacterial test results of other metal-oxide agents such as ZnO 2 [89], SiO 2 [90], and TiO 2 [91], the ZnO sol-gel film in this paper is estimated to be an excellent agent. Furthermore, satisfactory antibacterial activity of the synthesized ZnO sol-gel film was maintained even after the 120-min UVO treatment, as displayed in Figure 4c.…”
Section: Resultsmentioning
confidence: 99%
“…The SBF solution was prepared by dissolving NaCl, NaHCO 3 , KCl, MgCl 2 ·6H 2 O, CaCl 2 , Na 2 HPO 4 , and Na 2 SO 4 in ultra‐pure water buffered at pH 7.4 using 4‐(2‐hydroxyethyl)piperazine‐1‐ethanesulfonic acid hemisodium salt. Taking into account that the ratio of the exposed surface to the volume solution influences the reaction, a constant ratio was maintained as reported in the literature . The solution was replaced every 2 days to avoid depletion of the ionic species in the SBF due to the nucleation of biominerals on the samples.…”
Section: Methodsmentioning
confidence: 99%